Bayesian analysis of academic engagement in psychology students: differences according to sex and age - Fuster Guillen, Fiorella Gaby (2021)
Introduction: Engagement is a construct that arose in the opposite way to burnout and is understood as the state of physical and psychological well-being of an individual linked to an activity. Although initially it was investigated in the organizational area, in recent years it has been oriented towards education. Objective: The objective of the study was to analyze the differences in academic commitment according to sex and age in psychology students. Method: Comparative study of cross-sectional design, where 190 psychology students participated who answered the Utrecht Work Engagement Scale-Student (UWES-9S), selected by convenience sampling and inclusion criteria. Results: Bayesian analysis showed that, in the gender group, there is not enough information to support the alternative or null hypothesis (BF <3), while, in the age group, a moderate strength is evidenced for the null hypothesis (BF01 = 8.52, δ = .04, 95% CI = .31-.24). Conclusions: The findings showed that, regarding academic commitment, it was evidenced that there are no differences in the age group in psychology university students and, in relation to sex, there was greater uncertainty for both hypotheses, requiring a greater collection of data to His confirmation. The results of this study are preliminary.